A new encrypted image retrieval method based on feature fusion in cloud computing. (4th May 2020) - Chen, Jianhua; Qin, Jiaohua; Xiang, Xuyu; Tan, Yun
The traditional image retrieval has high requirements on the computing power and storage capacity of the platform, so the cloud server has become the preferred choice for outsourcing image retrieval. However, the cloud server is not completely reliable, and outsourcing image retrieval may bring many security, low retrieval accuracy, and privacy problems. In this paper, an encrypted image retrieval method based on feature fusion is proposed. Firstly, the images are encrypted by the encryption operator. Then, the feature extractor is designed, and the enhanced RGB feature and HSV histogram feature are extracted. Finally, the feature extractor and encrypted images are uploaded to the cloud server. The computation of similarity between images is done in the cloud. The experiments and security analysis show that the proposed method has good security and accuracy.